2015
DOI: 10.1007/s11046-015-9916-z
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution, Virulence Factors, and Antifungal Susceptibility Among Candida parapsilosis Complex Isolates Recovered from Clinical Specimens

Abstract: The Candida parapsilosis complex has emerged as an important fungal pathogen. In spite of this, relatively little is known about its characteristics. Thus, the purposes of this study were (1) to determine by BanI-RFLP-assay the occurrence of C. parapsilosis complex species among 81 clinical isolates primarily identified as C. parapsilosis; (2) to evaluate their in vitro production of virulence factors; and (3) to compare their susceptibility profiles, grown as planktonic cells and biofilms, against amphoterici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
3
20
0
1
Order By: Relevance
“…Of the seven C. metapsilosis isolates, five produced proteinase, and interestingly, one was found to produce both enzymes. Phospholipase production is not usual for this species; the absence of PL activity in C. metapsilosis isolates has been previously described 13 . Although the role of PL in Candida virulence remains unclear, some authors recognize the secretion of proteinases as an important virulence factor, which is immunogenic during infection and able to promote the degradation of host defense proteins 3 .…”
mentioning
confidence: 80%
“…Of the seven C. metapsilosis isolates, five produced proteinase, and interestingly, one was found to produce both enzymes. Phospholipase production is not usual for this species; the absence of PL activity in C. metapsilosis isolates has been previously described 13 . Although the role of PL in Candida virulence remains unclear, some authors recognize the secretion of proteinases as an important virulence factor, which is immunogenic during infection and able to promote the degradation of host defense proteins 3 .…”
mentioning
confidence: 80%
“…Similarly, additional studies reported that Ͼ88% of C. parapsilosis clinical isolates actively secreted these enzymes (168,(193)(194)(195). On the other hand, others reported a lower number (Ͻ37%) of clinical strains producing hydrolytic proteases (196)(197)(198)(199). Although there is wide variability among C. parapsilosis isolates in terms of Sap production, it is commonly agreed that isolates derived from host surfaces (e.g., skin or vaginal mucosa) are more likely to produce and secrete these enzymes than those obtained from systemic infections or from the environment.…”
Section: Hydrolytic Enzyme Productionmentioning
confidence: 95%
“…C. parapsilosis also secretes phospholipases albeit with wide intraspecies variation, with studies reporting that 9 to 90% of clinical isolates produce the enzyme (193,196,198,199). However, their contribution to pathogenicity is still a matter of debate, as there is no direct link between their expression and the degree of virulence.…”
Section: Hydrolytic Enzyme Productionmentioning
confidence: 99%
“…So, further studies are needed to better understand the characteristics, including putative virulence traits, drug resistance trends, especially of the two rarely isolated species, C. orthopsilosis and C. metapsilosis . A better knowledge could have clinical relevance, as it may be useful in guiding therapeutic decisions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%